2015
DOI: 10.1177/2333721415618858
|View full text |Cite
|
Sign up to set email alerts
|

Gait Speed and Variability for Usual Pace and Pedestrian Crossing Conditions in Older Adults Using the GAITRite Walkway

Abstract: Objectives: To determine gait characteristics of community-dwelling older adults at different speeds and during a crosswalk simulation. Methods: Twenty-two older adults completed walking trials at self-selected slow, usual, and fast paces, and at a crosswalk simulation, using the GAITRite walkway. These objective measures were complemented by self-report health and mobility questionnaires. Results: Gait speeds at self-selected slow, usual, and fast paces were 98.7 (18.1) cm/s, 140.9 (20.4) cm/s, and 174.0 (20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…A recent systematic review, for instance, reported mean walking speed requirements of 0.44, 0.73–0.78, and 1.32 m/s, in the large cities of Melbourne, Singapore, and Los Angeles, respectively [ 75 ]. However, considering the limited number of crossroads that were analyzed in these studies, it still seems adequate to compare older adult’s walking speed with the 1.2 m/s standard recommended by national traffic authorities, including the United States, Canada, the United Kingdom, Ireland, South Africa, and Switzerland [ 11 , 13 15 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review, for instance, reported mean walking speed requirements of 0.44, 0.73–0.78, and 1.32 m/s, in the large cities of Melbourne, Singapore, and Los Angeles, respectively [ 75 ]. However, considering the limited number of crossroads that were analyzed in these studies, it still seems adequate to compare older adult’s walking speed with the 1.2 m/s standard recommended by national traffic authorities, including the United States, Canada, the United Kingdom, Ireland, South Africa, and Switzerland [ 11 , 13 15 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to what intuitively might be assumed, aging itself is not a strong explanatory factor for the observable slowing of preferred gait speed in the older population. Healthy older adults walk at a speed that exceeds standards for crossing urban streets; furthermore, they are able to adopt a significantly faster gait in response to a crosswalk signal albeit this comes at the cost of increased gait variability [ 11 ]. It seems that especially potentially modifiable factors such as impairment of Instrumental Activities of Daily Living, physical inactivity and cardiovascular disease, are related to the observed slowing of walking speed in many older adults [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When needed, most healthy older people can adopt a faster speed sufficient to cross urban streets in summer conditions. A higher speed can also induce more variable gait in terms of step length and time variability [30]. There are indications that higher gait variability may increase the risk of falls [31].…”
Section: Discussionmentioning
confidence: 99%
“…The measurement method was based on a walking board of 5 m, which takes into account the acceleration and the deceleration section of the gait with a margin of 2 m each. Altogether, 9 m of gait was measured three times and the average value was calculated [33]. The spatiotemporal variables of the stance phase and the swing phase included gait speed, cadence, step length, stride length, stance time, and swing time.…”
Section: Gait Analysismentioning
confidence: 99%